1 Thực hiện phép tính
a)(2x-3)(x-2)
b) (x+3)2
c) (2x-3y)3
d)2x(x3-8)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Ta có x3 + y3 + z3 = 3xyz
<=> x3 + y3 + z3 - 3xyz = 0
<=> (x + y)3 - 3xy(x + y) + z3 - 3xyz = 0
<=> [(x + y)3 + z3] - 3xy(x + y + z) = 0
<=> (x + y + z)[(x + y)2 - (x + y)z + z2] - 3xy(x + y + z) = 0
<=> (x + y + z)(x2 + y2 + z2 + 2xy - xz - yz) - 3xy(x + y + z) = 0
<=> (x + y + z)(x2 + y2 + z2 - xy - xz - yz) = 0
<=> \(\orbr{\begin{cases}x+y+z=0\\x^2+y^2+z^2-xy-yz-zx=0\end{cases}}\)(1)
Khi x2 + y2 + z2 - xy - xz - yz = 0
<=> 2(x2 + y2 + z2 - xy - xz - yz) = 0
<=> 2x2 + 2y2 + 2z2 - 2xy - 2xz - 2yz = 0
<=> (x2 - 2xy + y2) + (y2 - 2yz + z2) + (x2 - 2xz + z2) = 0
<=> (x - y)2 + (y - z)2 + (x - z)2 = 0
<=> \(\hept{\begin{cases}x-y=0\\y-z=0\\z-x=0\end{cases}}\Leftrightarrow x=y=z\)(2)
Từ (2) (1) => đpcm
\(\left(2x-3\right)\left(x-2\right)\)
\(=2x^2-4x-3x-6\)
\(=2x^2-7x-6\)
\(\left(x+3\right)^2\)
\(=x^2+2x.3+3^2\)
\(=x^2+6x+9\)
\(\left(2x-3y\right)^3\)
\(=\left(2x\right)^3-3.\left(2x\right)^2.3y+3.2x.\left(3y\right)^2-\left(3y\right)^3\)
\(=8x^3-36x^2y+54xy^2-27y^3\)
\(2x\left(x^3-8\right)\)
\(=2x^4-16x\)